EFEKTIVITAS PENERAPAN MODUL AJAR BERBASIS GRAPHIC ORGANIZER PADA MATERI KALOR DAN PERPINDAHANNYA - Jihandris, Egidius Elvin; Maria S, Haratua Tiur; Hidayatullah, Muhammad Musa Syarif (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study is to find out the effectiveness of a teaching module using graphic organizers on student learning outcomes. This study is an experimental study. The research design adopts the preexperimental design of "one group pre-test-post-test design" design model. The population of this study included all VII B students, a total of 30 students. The sampling method used simple random sampling technique, therefore VII B was selected as the sampling study. The data collection methods used were testing, recording and observation. The research results show that the average score of the experimental class in the pre-test was 39.00, and the average score in the post-test was 81.00. The effect size results obtained therefore met the moderate criterion of 3.05. Based on the above introduction, the use of graphic organizer-based teaching modules can improve the enthusiasm and transfer learning outcomes of grade 7 students at SMP Negeri 1 Sungai Raya